Self-regulation of Exercise Behavior in the TIGER Study. Issue 1 (6th December 2013) - Dishman, Rod K.; Jackson, Andrew S.; Bray, Molly S.
Abstract: Objective: This study aimed to test experiential and behavioral processes of change as mediators of the prediction of exercise behavior by two self-regulation traits, self-efficacy and self-motivation, while controlling for exercise enjoyment. Methods: Structural equation modeling was applied to questionnaire responses obtained from a diverse sample of participants. Objective measures defined adherence (928 of 1, 279 participants attended 80 % or more of sessions) and compliance (867 of 1, 145 participants exercised 30 min or more each session at their prescribed heart rate). Results: Prediction of attendance by self-efficacy (inversely) and self-motivation was direct and also indirect, mediated through positive relations with the typical use of behavioral change processes. Enjoyment and self-efficacy (inversely) predicted compliance with the exercise prescription. Conclusions: The results support the usefulness of self-regulatory behavioral processes of the transtheoretical model for predicting exercise adherence, but not compliance, extending the supportive evidence for self-regulation beyond self-reports of physical activity used in prior observational studies.